On-the-match price renegotiation: Evidence from Pakistan's import data - Liaqat, Zara; Hussain, Karrar; Khan, Bilal M. (Economics letters, 2021)
Using matched importer–exporter transaction level trade data, this study offers evidence quantifying the extent of price dispersion within a foreign seller across importing firms in Pakistan. Furthermore, we examine the key mechanisms describing the pricing strategy of foreign sellers of narrowly defined product categories. We show that, within a given firm-to-firm network, importers tend to renegotiate prices on-the-match, resulting in prices to drop over time. Although these price adjustments do not differ substantially for differentiated products, foreign sellers of differentiated goods charge a significantly higher price to their newly acquired and one-shot buyers.
CRIS-Team Scopus Importer:2021-04-16
Keywords: Firm-to-firm trade; Price discrimination; Transactional relationships